The functional aspect of aphorisms in German and Russian linguistic traditions - Popova , Yekaterina Aleksandrovna (The Lingua Spectrum, 2026)
This article adopts a comparative linguistic approach to examining the function of aphorisms in German and Russian. Aphorisms are considered distinct, compact texts with a high level of semantic depth, clear pragmatic focus, and striking stylistic expressiveness. Drawing on linguistic and literary studies, the paper analyses how aphorisms function in these languages. It summarises existing aphorism definitions, identifies their genre and semantic-pragmatic features, and categorises aphoristic unit functions. Particular focus is given to distinguishing the obligatory, optional, and unique functions of aphorisms in Russian linguistics, as well as analysing the functional impact of aphorisms in German. The paper provides a thorough comparison of the functional classification of aphorisms and an analysis of their pragmatic impact, based on extensive German-language sources. The results confirm the polysemy and universality of the aphorism as a means of expressing generalised experience and influencing readers, emphasising its significant role in creating stylistically rich discourse. Despite national and cultural specificity, the functional potential of aphorisms was found to be largely similar.